The roles of miRNA in inflammatory reaction of infectious diseases - Ruitao ZOU; Guiyue CAI; Xiaoxuan CHEN; Zhijia LI; Rongyi CHEN (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
MiRNA is a class of non-coding RNAs with regulatory functions that regulate gene expression after transcription. In recent years, more and more evidence has shown that pathogens regulate the expression of relevant inflammatory factors though miRNA in infection diseases which can affect the occurrence, development and outcome of the disease. However regulatory mechanism is unclear. Therefore, we review the research advance of miRNA in inflammatory response of infectious diseases.